GREAT MILITARY BUILDINGS AND THEIR BATTERIES DEFEND THE CANAKKALE STRAIT DURING 15th-18th CENTURIES - Daggulu, Ibrahim Basak (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2007)
The buildings which kept their exsistance throughout the centuries are generally the buildings with monumental qualites or the ones which kept their functionality through long periods of time. Inconsiderable advancement in the field of defending technologies between 15(th) and mid of 19(th) centuries let especially military buildings such as fortresses, blockhouses and batteries to sustain their existence with minor changes throughout that era. The building of the fortresses defending Dardanelles has been started in the 15(th) century when artillery started to took place in the battle fields as the main weapon. These fortresses kept Dardanelles impassable for nearly four hundred years, defending the Ottoman capital Istanbul against very serious threats. Although these buildings and the artillery contained by them were neglected in the periods of time passed with seldom or complete inexistance of treads; the artillery and the fortress buildings were reinforced and restored as much as possible in the times of crisis. The little progress of artillery techniques in the past centuries is one of the most important reasons for the fortress buildings to sustain their originality until a very near past. However the remarkable advancement achieved in the field of artillery tecniques in the second half of the 19(th) century left the fortresses outdated and inoperative. These fortresses have been damaged both by the upgrading and reinforcement Works in those years and also by becoming the target of modern and strong weapons in the wars. This study aims to analyse and document by visualizing functional state of these buildings in the 17th century when they were most effective and completly original; benefiting the visual and writen historical documents.
Keywords: Military architecture; Defensive buildings; Dardanelles; Architecture